Post-photo-reportage and the challenges of the new audiovisual narratives - Renó, Denis Porto [UNESP] (My University, 2020)
Photojournalism is a modality that was rethought with the arrival of navigable digital environments, as well as photography itself, redefined by Fontcuberta (2016) as post-photography. Based on this issue, this study offers qualitative results related to a growing form of journalistic narrative production, which includes audiovisual and photographic content, in an essentially imaginary composition, known as post-photojournalism. This study is the result of applied research, which presents the analysis of the work Prismas de Marrakech, created particularly for the development of this research. In conclusion, it highlighted the definitions of the concept of post-photojournalism, which reshapes the very production of imaginary journalistic reporting. With the results presented here, the aim is for the format to be continuously studied, given its cognitive capacity to offer the user an intense narrative experience based on the image. It is also expected that the conclusion from this study will aid in developing new studies related to photography, considering the growing space occupied by journalism, increasingly present in everyday media.
Posfotorreportaje y los desafíos de las nuevas narrativas audiovisuales
Pós-fotorreportagem e os desafios das novas narrativas audiovisuais
Keywords: Audiovisual; Communication; Média ecology; Photography